ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN PERGANTIAN CHIEF EXECUTIVE OFFICER (CEO) DILIHAT DARI ABNORMAL REURN SAHAM - Yunita Adelia Putri; Nur Diana; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT This research was conducted with the aim of: 1). This research aims to know the market react to the announcement of the turn of the Chief Executive Officer (CEO) are reflected in the Abnormal Return.The population used in this study are all companies listed on the Indonesia stock exchange (BEI) in 2014-2018. The selection of the sample using a purposive sampling. Based on the criteria, obtained 36 companies sampled in this study. The methods used in this study using a different Test methods.Based on the results of the analysis can be put forward some conclusions as follows: 1) t indicates that the test results Announcement turn CEO had no significant effects against Abnormal return. This is shown by the value of the sig above 0.05 i.e. of 0.103. 2). turn CEO Announcement is not significant effects against the return of shares. This is shown by the value of the sig above 0.05 i.e. of 0.203. Keywords: announcement of the turn of the Chief executive Officer (CEO), Abnormal Return, a Return of shares.